Pengembangan Model Perilaku Pemimpin Berwawasan Budaya Lokal Untuk Meningkatkan Efektivitas Organisasi Di Eks Karesidenan Banyumas - Daryono Daryono (BADAN PENERBIT STIEPARI PRESS, 2023)
Engable development as a dialogue and diagnostic method for provides a framework for the Engagement Agency's local culture and leadership behavior that will enable the emergence and development of a culture of engagement across local leadership behavior and culture in the Banyumas ex-resident. The diagram below provides a visual representation of the data sources and analysis methods used. Emphasizing that Engagement is a meta-lens covering all elements of engagement and engagement practices, including the Engage Scholarship. Engagement can be formal or informal, involving an interactive, reciprocal, two-way relationship built on trust, connectivity and shared meaning. Engagement practices are many and varied, including collaboration, leadership, and partnership activities. Leader behavior and local culture in the former Banyumas occupation is an engagement activity that specifically connects the behavior of local leaders and culture in the former Banyumas residence with individuals and communities in the former Banyumas residence, including business, industry, social and cultural groups, and government, within and outside the territory. The involvement of the behavior of local leaders and culture in the former Banyumas residence was generally manifested through culture program activities